2021
DOI: 10.1016/j.bbih.2021.100251
|View full text |Cite
|
Sign up to set email alerts
|

The unfolding palette of COVID-19 multisystemic syndrome and its neurological manifestations

Abstract: Although our current knowledge of the pathophysiology of COVID-19 is still fragmentary, the information so far accrued on the tropism and life cycle of its etiological agent SARS-CoV-2, together with the emerging clinical data, suffice to indicate that the severe acute pulmonary syndrome is the main, but not the only manifestation of COVID-19. Necropsy studies are increasingly revealing underlying endothelial vasculopathies in the form of micro-haemorrhages and micro-thrombi. Intertwined with defective antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 275 publications
(302 reference statements)
0
22
0
5
Order By: Relevance
“…This may indicate a different etiology of the myelopathies in these patients. SARS-CoV-2 infection has been shown to cause both microhemorrhages and small vessel micro-thromboses through endothelial damage, coagulopathies, and antiphospholipid antibody-like syndrome (McFadyen et al 2020 ; Salamanna et al 2019 Jul 3 ; Barrantes 2021 ). Small vessel spinal cord strokes may explain the lack of apparent radiologic findings, lack of response to immunotherapeutic agents, and less recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate a different etiology of the myelopathies in these patients. SARS-CoV-2 infection has been shown to cause both microhemorrhages and small vessel micro-thromboses through endothelial damage, coagulopathies, and antiphospholipid antibody-like syndrome (McFadyen et al 2020 ; Salamanna et al 2019 Jul 3 ; Barrantes 2021 ). Small vessel spinal cord strokes may explain the lack of apparent radiologic findings, lack of response to immunotherapeutic agents, and less recovery.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown in rodents that SARS-CoV-2 infects non-neural cells in the olfactory epithelium rather than olfactory neurons, which could be attributed to the lack of expression of ACE2 in these cells ( Brann et al, 2020 , Bryche et al, 2020 ). In contrast, a recent study found viral particles throughout olfactory neuron projections and in the olfactory bulb of a few patients ( Meinhardt et al, 2020 ) and other hypotheses have been proposed ( Barrantes, 2021 ). Therefore, due to these conflicting findings, it is still debatable whether the mechanism of SARS-CoV-2 invasion in the CNS is via olfactory neurons.…”
Section: Introductionmentioning
confidence: 83%
“…Im Verlauf der Pandemie wurden neben den akuten Manifestationen einer COVID-19-Infektion Symptome untersucht, die eine lĂ€nger anhaltende chronische Verlaufsform der Erkrankung mit neurologischen/neuropsychiatrischen, pulmonalen, kardialen und gastrointestinalen Beschwerden vermuteten lassen [ 4 ]; Letztere werden hier nicht weiter ausgefĂŒhrt. Das Post-COVID-19-Syndrom kann sich dabei als anhaltende COVID-19-Symptomatik (z.…”
Section: Langzeitfolgenunclassified